2014
DOI: 10.1073/pnas.1410796111
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic disorder as a generalizable strategy for the rational design of highly responsive, allosterically cooperative receptors

Abstract: Control over the sensitivity with which biomolecular receptors respond to small changes in the concentration of their target ligand is critical for the proper function of many cellular processes. Such control could likewise be of utility in artificial biotechnologies, such as biosensors, genetic logic gates, and "smart" materials, in which highly responsive behavior is of value. In nature, the control of molecular responsiveness is often achieved using "Hilltype" cooperativity, a mechanism in which sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 41 publications
(50 reference statements)
1
56
0
1
Order By: Relevance
“…Created using well-established in vitro selection methods (16,17), aptamers can be generated that bind a wide range of analytes (18) and can be rationally reengineered such that they undergo a large-scale conformational change upon binding these analytes (19) over arbitrarily broad (20,21) or narrow (20,22) concentration windows. E-AB sensors use this conformational change to generate an easily measureable electrochemical signal without the need for the target to undergo a chemical transformation (23).…”
Section: Significancementioning
confidence: 99%
“…Created using well-established in vitro selection methods (16,17), aptamers can be generated that bind a wide range of analytes (18) and can be rationally reengineered such that they undergo a large-scale conformational change upon binding these analytes (19) over arbitrarily broad (20,21) or narrow (20,22) concentration windows. E-AB sensors use this conformational change to generate an easily measureable electrochemical signal without the need for the target to undergo a chemical transformation (23).…”
Section: Significancementioning
confidence: 99%
“…We demonstrate this approach using an otherwise noncooperative (bottom, left) cocaine-binding aptamer and achieved a cooperative response covering just 13-fold (bottom right). Figure adapted with permission from ref 53. Copyright 2014 National Academy of Sciences.…”
Section: Figurementioning
confidence: 99%
“…This implies that a transition of CBSA assembly from 10% to 90% requires only a 16-fold increase in target concentration, compared to its parent split aptamers which require an 81-fold increase. 28 NUPACK analysis 37 of the DIS-binding CBSA sequences demonstrated that both fragments are predominantly un-assembled (99%) in the absence of target under our experimental conditions, but DIS-SF exists primarily as a duplexed structure (Supporting Information, Figure S3A). Therefore, binding of the first target to DIS–CBSA-4536 should open up the DIS-SF duplex, facilitating binding of a second DIS molecule to the CBSA, This results in a high level of cooperativity.…”
Section: Resultsmentioning
confidence: 87%